EFFECTS OF RESISTANT TRAINING DURING RADIOTERAPIC TREATMENT IN WOMEN WITH BREAST CANCER: A SYSTEMATIC REVIEW: uma revisão sistemática - Siqueira, Gabriel Dutra de Jesus; Marques, Vitor Alves; Alves, Rafael Ribeiro; Silva, Weder Alves da; Vieira, Carlos Alexandre (International Journal of Movement Science and Rehabilitation, 2020)
Aim: To analyze the effects of resistance training (RT) during radiotherapy treatment in women with breast cancer. Methods: The searches were performed in the databases PubMed, Bireme, Web of Science and Scopus. All articles published up to February 2019 were considered. Inclusion criteria were: articles in English, Portuguese and Spanish; during radiotherapy treatment; and with outcomes related to muscle performance, body composition, psychosocial parameters and blood markers. Results: Three studies were included. These three articles involved the participation of 404 breast cancer patients receiving radiotherapy, with the average age close to 56 years in these studies. The three studies scored six on the methodological quality assessment using the PEDro scale. In the studies, the effects of RT on levels of inflammatory markers, muscle strength performance, fatigue, pain and quality of life were verified. Conclusion: RT seems to be efficient for muscle strength gains, reduction of fatigue and pain levels, and to promote the maintenance of inflammatory markers during radiotherapy treatment.